2000
DOI: 10.1053/euje.2000.0010
|View full text |Cite
|
Sign up to set email alerts
|

Left and Right Atrial Volume by Freehand Three-dimensional Echocardiography: In Vivo Validation Using Magnetic Resonance Imaging

Abstract: Freehand 3D echocardiography using the line of intersection display for guidance of image positioning and a polyhedral surface reconstruction algorithm is a valid, accurate, reproducible method for determining left and right atrial volume in humans that is comparable to magnetic resonance imaging and is superior to current ID and 2D echocardiographic techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
132
0
10

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(148 citation statements)
references
References 22 publications
6
132
0
10
Order By: Relevance
“…al., used a freehand scanning technique which relied on manually tracing multiple cross-sectional areas through the left atrium and combining them in a polyhedral surface reconstruction algorithm to generate a volume. 14 In this study 3D-TTE demonstrated the best correlation (r=0.91) with the smallest bias and narrowest limits of agreement (5 ± 22ml), but this was only marginally better than 2D-TTE (r=0.87, 14.4 ± 24ml).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…al., used a freehand scanning technique which relied on manually tracing multiple cross-sectional areas through the left atrium and combining them in a polyhedral surface reconstruction algorithm to generate a volume. 14 In this study 3D-TTE demonstrated the best correlation (r=0.91) with the smallest bias and narrowest limits of agreement (5 ± 22ml), but this was only marginally better than 2D-TTE (r=0.87, 14.4 ± 24ml).…”
Section: Discussionmentioning
confidence: 94%
“…Efforts to improve the assessment of left atrial volume by echocardiography should concentrate on better techniques for defining the endocardium that outlines the left atrial chamber. Indeed, the only study to date that demonstrated excellent correlation with minimal bias imaged the left atrium from the parasternal window 14 , thus placing the left atrium much closer to the ultrasound transducer. Future studies exploring the feasibility of this approach with real-time 3D-TTE are needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Além disso, a curva de variação do volume ao longo do ciclo cardíaco, gerada digitalmente, permite a seleção do volume em qualquer ponto da curva, ou fase do ciclo car-díaco (Figura 5). Assim, a E3DTR é um método ideal para avaliar o volume do AE, sendo comparável à ressonância magnética nuclear 42 , com pequena varia-bilidade interobservador 43 , sendo esta menor do que a da ressonância 44 .…”
Section: Avaliação Volumétrica Do Aeunclassified
“…The recent advent of real-time three-dimensional echocardiography (RT3DE) has enabled cardiologists to obtain LA volumes and functional parameters based on real anatomical conditions and has been shown to be superior to conventional two-dimensional 2D techniques [11][12][13][14]. Previously published studies assessing LA functional parameters using RT3DE, however, had to rely on semiautomatic contour tracing algorithms originally developed for the left ventricle [15][16][17].…”
Section: Introductionmentioning
confidence: 99%